1999
DOI: 10.1038/sj.onc.1202495
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation between SMAD and NF-κB in growth factor regulated type VII collagen gene expression

Abstract: We have previously demonstrated that transforming growth factor-b (TGF-b) and pro-in¯ammatory cytokines, such as tumor necrosis factor-a (TNF-a) or interleukin-1b, synergistically enhance the expression of type VII collagen gene (COL7A1) in human dermal ®broblasts in culture (Mauviel et al., 1994). Recently, we identi®ed a SMAD-containing complex, rapidly induced by TGF-b and binding the region [7496/7444] of the COL7A1 promoter, responsible for COL7A1 gene transactivation (Vindevoghel et al., 1998a). In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
1
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 34 publications
3
49
1
1
Order By: Relevance
“…Upon ligand activation, the heteromeric complex of receptorspeci®c Smad3 and Smad4 translocate into the nucleus and bind to speci®c elements in target promoters, resulting in activation of their transcription (Heldin et al, 1997). We and others have previously demonstrated that Smad3 transactivated the collagen promoter and enhanced their response to TGF-b in human primary ®broblasts (Vindevoghel et al, 1998;Kon et al, 1999;Chen et al, 1999). The mechanisms that control transactivation of collagen and other cellular genes by the DNA-bound Smad complex remain poorly understood, and are likely to involve the interaction of Smads with coactivators.…”
Section: Discussionmentioning
confidence: 99%
“…Upon ligand activation, the heteromeric complex of receptorspeci®c Smad3 and Smad4 translocate into the nucleus and bind to speci®c elements in target promoters, resulting in activation of their transcription (Heldin et al, 1997). We and others have previously demonstrated that Smad3 transactivated the collagen promoter and enhanced their response to TGF-b in human primary ®broblasts (Vindevoghel et al, 1998;Kon et al, 1999;Chen et al, 1999). The mechanisms that control transactivation of collagen and other cellular genes by the DNA-bound Smad complex remain poorly understood, and are likely to involve the interaction of Smads with coactivators.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Smads may aect epidermal dierentiation via TGFb-independent pathways. Potential candidates for these TGFb-independent genes include calmodulin, NF-kB, and the vitamin D receptor, all of which have been shown to play an important role in epidermal dierentiation (Bikle and Pillai, 1988;Hu et al, 1999;Li et al, 1999;Ma et al, 1997;Roop et al, 1987;Rougui et al, 1996;Takeda et al, 1999), and to interact directly with Smads (Kon et al, 1999;Yanagisawa et al, 1999;Zimmerman et al, 1998). Therefore, it will be worthwhile to further determine the exact role of Smads in epidermal dierentiation in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies to date examining the function of Smad proteins in TGF-␤1 signaling have focused on genes that are transactivacted by TGF-␤1, including plasminogen activator inhibitor (PAI)-1 (27), collagen-I (28) and collagen-VII (29,30), and the cyclin-dependent kinase inhibitors p15 (31) and p21 (32,33). In contrast to TGF-␤1-mediated gene transactivation, the mechanism by which TGF-␤1 inhibits gene transcription is not well characterized.…”
Section: Transforming Growth Factor (Tgf)-␤1mentioning
confidence: 99%